Neoliberal reform and family engagement in schools: An intersectional gender analysis - Nygreen, Kysa (Policy Futures in Education, 2019)
This article presents an exploration of the work of family engagement in a racially- and linguistically-diverse, high-poverty, urban school district in a state of continuous neoliberal reform. Drawing from qualitative research methods, it is argued that family engagement is being reshaped by the imperatives of educational neoliberalization while, at the same time, remaining out of touch with the needs and concerns of families who are racially stigmatized, linguistically diverse, and experiencing extreme economic insecurity. It is further argued that school personnel charged with family engagement carry out exploited, invisible, and emotional tasks that increase in quantity and intensity as the social safety net declines under neoliberalism. Applying an intersectional gender analysis of emotional labor and the re-privatization of social reproduction offers an illustration of how family engagement in neoliberal schools both exploits and reinforces hierarchies of race–class–gender while obscuring these processes through neoliberal discourses of individual responsibilization. © The Author(s) 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; inégalités; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail émotionnel; états-unis